Cover Feature: Highly Charged Ruthenium(II) Polypyridyl Complexes as Effective Photosensitizer in Photodynamic Therapy (Chem. Eur. J. 45/2019). Issue 45 (3rd July 2019) - Conti, Luca; Bencini, Andrea; Ferrante, Camilla; Gellini, Cristina; Paoli, Paolo; Parri, Matteo; Pietraperzia, Giangaetano; Valtancoli, Barbara; Giorgi, Claudia
Abstract : Ru II polypyridyl complexes are promising candidates for application in the field of photodynamic therapy, thanks to their rich chemical physical repertoire. This work reports on two novel Ru II and Ru II /Cu II mixed polypyridyl compounds which feature great cellular uptakes and can generate highly cytotoxic species when light‐activated. The study highlights the key role of the Fenton active Cu II center within the macrocycle residue of such compounds that would play a synergistic action with light activation in the formation of powerful Reactive Oxygen Species. More information can be found in the Full Paper by L. Conti, C. Giorgi, et al. on page 10606 .